MHD and thermal radiation effects on exponentially accelerated isothermal vertical plate with uniform mass diffusion - Muthucumaraswamy, Rajamanickam; Visalakshi, V. (Zielona Góra: Uniwersytet Zielonogórski)
Thermal radiation effects on an unsteady free convective flow of a viscous incompressible flow of a past an exponentially accelerated infinite isothermal vertical plate with uniform mass diffusion in the presence magnetic field are considered. The fluid considered here is a gray, absorbing-emitting radiation but a non-scattering medium.
Keywords: radiation; isothermal; vertical plate; mass diffusion; magnetic field